Edge Computing: Revolutionizing Real-Time Financial Analytics through Low-Latency Processing - Bharath kumar Gaddam (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the transformative impact of edge computing on financial analysis systems, focusing on its role in achieving ultra-low latency processing and enhanced real-time decision-making capabilities. The article explores the architectural framework of edge computing in financial services, analyzing its implementation across critical applications including high-frequency trading, fraud detection, and risk management systems. Through detailed performance analysis, this study demonstrates significant improvements in processing times, with latency reductions of up to 80% compared to traditional cloud-based solutions, while maintaining robust security measures and regulatory compliance. The investigation encompasses both theoretical foundations and practical applications, addressing key implementation challenges such as technical constraints, security considerations, and cost implications. The article reveals that edge computing architectures can achieve sub-millisecond latency for critical financial operations, with some high-frequency trading applications reaching latencies as low as 100 microseconds. This article also highlights emerging trends and future directions, including the integration of quantum computing and artificial intelligence at the edge, suggesting substantial potential for further innovation in financial services technology. The article concludes that edge computing represents a fundamental shift in financial data processing, offering significant competitive advantages for institutions that successfully implement these solutions while navigating the associated technical and operational challenges.